2009
DOI: 10.33899/rjs.2009.39959
|View full text |Cite
|
Sign up to set email alerts
|

Indirect Spectrophotometric Method for the Determination of Mefenamic Acid in Pharmaceutical Formulations*

Abstract: A simple, sensitive and accurate spectrophotometric method for the determination of mefenamic acid in pure form and in some pharmaceutical formulations was developed. The method is based on the oxidation of mefenamic acid by iron(III), and subsequent complexation of iron(II) with o-phenanthroline, forming a red-colored complex (ferroin) having the maximum absorbance at 510 nm. Beer's law is obeyed in the concentration range of 0.4-2.0 µg\ml, the molar absorptivity and Sandell's sensitivity are 2.9×10 4 L.mol -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The method involves the oxidation of MFA by iron(III) followed by the complexation of iron(II) with ophenanthroline resulting in a red-colored complex (ferroin) with a maximum absorbance at 510 nm. Beer's law is obeyed in the concentration range of 0.4-2.0 µg/ml [21]. Raju Chandra et al developed validation for the estimation of MFA from marketed tablet and the λmax was found to be 370 nm, the limit of detection and limit of quantification was 0.3 and 0.9 ppm respectively.…”
Section: Spectroscopy Techniques Of Mfamentioning
confidence: 99%
“…The method involves the oxidation of MFA by iron(III) followed by the complexation of iron(II) with ophenanthroline resulting in a red-colored complex (ferroin) with a maximum absorbance at 510 nm. Beer's law is obeyed in the concentration range of 0.4-2.0 µg/ml [21]. Raju Chandra et al developed validation for the estimation of MFA from marketed tablet and the λmax was found to be 370 nm, the limit of detection and limit of quantification was 0.3 and 0.9 ppm respectively.…”
Section: Spectroscopy Techniques Of Mfamentioning
confidence: 99%
“…Through repeatable and accurate timing, the FI approach can measure the properties of metastable and transitory species. Multiple measurements developed for clinical, pharmacological, dietary, and environmental studies have demonstrated the value of FI methods for regular analysis [10,[16][17][18][19][20][21][22][23][24][25][26]. When the reagents used are expensive, and the model is cheap and available in large quantities, it is preferable to reverse the injection process.…”
Section: Introductionmentioning
confidence: 99%